WACANA ISBAL DALAM MEME HADIS; ANALISIS KONTEN PADA AKUN FACEBOOK @produsensirwal - Chamimudin, Anang (Universum, 2023)
Wearing cingkrang pants is a sunnah that can be found in many hadith books. Many scholars have tried to examine the sunnah to get the correct understanding. However, over time the culture has changed. Such as the invitation to wear cingkrang pants and leave Islamic law circulating on social media. Unfortunately there is no detailed explanation to explain the purpose of the sunnah. In order to clarify the understanding of the concept of isbal in the Prophet's hadith, the researcher compiled an article that explored the meaning of isbal in the hadith memes by comparing it with the opinions of the scholars regarding the Prophet's hadith regarding isbal. This type of research includes qualitative research with the object of the Facebook account @produsensirwal. The analytical method used is content analysis. From a search of the Facebook account @produsensirwal, it is known that the concept of isbal in the hadith meme posted by the Facebook account @produsensirwal is that wearing clothes that extend above the ankles is haram. But on the other hand, the Facebook account @produsensirwal also uses the hadith meme about isbal to promote its wares, namely sirwal trousers. Of course, this is unacceptable considering the way the Facebook account @produsensirwal uses a hadith meme that is not accompanied by a detailed explanation. Moreover, the Facebook account @produsensirwal also takes advantage of the hadith meme about isbal as a marketing strategy under the guise of religion.